The Relationship between Obstructive Sleep Apnea (OSA) and Adherence of Antihypertensive Consumption in Regular Hemodialysis Patient - Lubis, Afrilia Rosada; Muzasti, Riri Andri (Talenta Publisher, 2019)
Background. Based on the Indonesian Renal Registry (IRR) data in 2015, the highest incidence of comorbidities in hemodialysis patients in Indonesia was hypertension (50%). Obstructive Sleep Apnea (OSA) is one of the causes of secondary hypertension, the characteristics of hypertension in OSA are more resistant to treatment. One of the causes of resistant hypertension is patient non-compliance with the consumption of antihypertensive drugs. Aim. To determine the relationship of adherence of consumption of antihypertensive drugs with obstructive sleep apnea in regular HD patients. Method. This cross-sectional study involved 89 outpatients in HD units at the Rasyida Kidney Hospital in 2018. Data was obtained through interview using the STOP-BANG questionnaire to assess the of risk of OSA and using Morisky Medication Adherence Scale (MMAS) questionnaire to measure the compliance of drug consumption. Results.The prevalence of OSA in HD patients was (39.3%). There was no significant relationship between adherence with drug consumption and OSA risk, but in bivariate analysis, age (p = 0.0001), body mass index (BMI) (p = 0.001), and gender (p = 0.03) were significantly related to OSA. In multivariate, age and BMI were significantly associated with OSA (OR: 6.449, 95% CI 2.246 ± 18.520, p = 0.001; OR: 6.130, 95% CI 2.105 ± 17.849, p = 0.001). Conclusion. OSA was not statistically related to adherence to antihypertensive drug consumption in HD patients but was significantly associated with age and BMI. Keyword. Adherence to antihypertensive consumption, hemodialysis, obstructive sleep apnea.